MiR-3074-5p Promotes the Apoptosis but Inhibits the Invasiveness of Human Extravillous Trophoblast–Derived HTR8/SVneo Cells In Vitro. (May 2018) - Gu, Yan; Shi, Yan; Yang, Qian; Gu, Wen-Wen; He, Ya-Ping; Zheng, Hua-Jun; Zhang, Xuan; Wang, Jian-Mei; Wang, Jian
Objective: The objective of this study was to observe the effects of the overexpression of miR-3074-5p in human trophoblast cells in vitro. Design: Experimental in vitro study in HTR8/SVneo cells. Methods: HTR8/SVneo cells were transfected with miR-3074-5p mimic. The cell apoptosis and invasion were measured via flow cytometry and transwell assay, respectively. The expression levels of P53, Cyclin Dependent Kinase Inhibitor 1B (P27), BCL-2, BCL2 associated X (BAX), and BCL2 like 14 (BCL-G) in HTR8/SVneo cells were determined by Western blot. The alterations in gene expression profile of HTR8/SVneo cells were evaluated by complementary DNA microarray assay, and the differential expressions of dihydrolipoamide S-succinyltransferase (DLST), growth-associated protein 43 (GAP43), runt-related transcription factor 2 (RUNX2), and C-C type chemokine receptor 3 (CCR3) were validated by Western blot. Biofunctions of these differentially expressed genes were enriched by Gene Ontology analysis. Results: The overexpression of miR-3074-5p in HTR8/SVneo cells promoted cell apoptosis but inhibited cell invasion, being accompanied by the significantly elevated expressions of P27, BCL-2, and BCL-G. Meanwhile, an increased expression of P27 and P57 was also detected in a small sample size of placental villi of recurrent miscarriage (RM) patients. Totally, 411 genes and 397 genes were screened out, respectively, to be downregulated or upregulated at least by 2-folds in miR-3074-5p overexpressed HTR8/SVneo cells. These differentially expressed genes were involved in several important functions related to pregnancy. Subsequently, the reduced expressions of DLST and GAP43 proteins, as well as the increased expressions of CCR3 and RUNX2 proteins, were validated in miR-3074-5p overexpressed HTR8/SVneo cells. Conclusion: These data suggested a potential contribution of miR-3074-5p in the pathogenesis of RM by disturbing the normal activities of trophoblast cells.